Towards a fusion of horizons: Thematic contours for an urban public theological praxis-agenda in South Africa - Beer, Stephan de (HTS teologiese studies, 2014)
This article proposes a ‘fusion of horizons’ in constructing urban public theologies in South Africa. This is done through the introduction of five interrelated themes that have emerged from the on-going knowledge and idea production by a distinguishable counterpoint in contemporary scholarly, intellectual and activist engagement with the urban, in the authors’ own South African context but also wider internationally. In advancing a praxis-agenda for urban public theology, the authors subsequently identify the following, albeit not exhaustive, themes: southern urbanisms and the factor of unprecedented urban migration; ‘right to the city’ and urbanisation from below; a reclaiming of the commons; the making of ‘good cities’; and actors of faith in relation to urban social life.